Sublingual immunotherapy vs placebo in the management of grass pollen‐induced allergic rhinitis in adults: A systematic review and meta‐analysis. (9th October 2020) - Boldovjáková, Dominika; Cordoni, Sara; Fraser, Craig John; Love, Aimee Beth; Patrick, Lorna; Ramsay, Gary James; Ferguson, Aaron Stephen James; Gomati, Anas; Ram, Bhaskar
Abstract: Introduction: Allergic rhinitis (AR) is a common inflammatory condition of the nasal mucosa affecting approximately 20% of the population worldwide. Current therapies include intranasal antihistamines, corticosteroids, subcutaneous and sublingual immunotherapy (SLIT). This review and meta‐analysis assess the efficacy of SLIT in the management of grass pollen‐induced AR in adults. Methods: Ovid EMBASE, Ovid EBM Reviews, Cochrane Central Register of Controlled Trials, Ovid MedLine and PubMed were searched using the following terms: 'sublingual immunotherapy', 'SLIT', 'rhinitis', 'allergic rhinitis', 'rhinosinusitis' and 'rhino‐conjunctivitis'. All included studies were double‐blind, placebo‐controlled and randomised trials. Primary outcome was symptom score and secondary outcome included quality of life and safety profile. Meta‐analysis of symptom improvement was carried out. Results: Six studies were identified with 979 subjects randomly allocated to SLIT and 992 to a placebo control. All studies reported an improvement in symptoms with SLIT, with five reaching statistical significance ( P < .05). Four studies reported statistically significant improvement in quality of life ( P < .05). Oral pruritus was the most common adverse event reported. The overall risk of bias was high in 50% of the studies. Conclusions: Sublingual immunotherapy was a safe and effective treatment for grass pollen‐induced AR in adults, and therefore, consideration should be given to its use for moderate‐to‐severe disease in the UK‐wide population.